Identifikasi Alat Permainan Edukatif Dalam Mengembangkan Sains Sederhana Pada Anak Usia Dini Di Kecamatan Kayangan Kabupaten Lombok Utara - Ni Wayan Putri Widnyani; Gunawan Gunawan; Baik Nilawati Astini; Ni Luh Putu Nina Sriwarthini (Indonesian Journal of Elementary and Childhood Education, 2023)
Educational game tools are learning tools that can be used to develop various aspects of child development such as cognitive, language, physical-motor, artistic, and social-emotional development as well as children's religion and morals. Science in early childhood is a variety of things that can stimulate children to increase their curiosity, so as to bring up thoughts and actions such as observing, thinking, and linking between concepts or events. The purpose of this study is to identify educational game tools that can be used in developing simple science in early childhood in the Kayangan sub-district. This research uses a qualitative descriptive research type with a survey method. The research subjects consisted of 8 kindergarten educators. The results of this study indicate that there are six educational game tools that can be used in developing simple science in early childhood, namely five indoor APE including homemade compasses, APE mixing colors from food coloring, APE inflatable balloons, experiments to know the taste of kitchen ingredients, science experiments green beans, and cotton, as well as an outdoor APE, namely a slide. Based on the estimated time used, slides and color mixing APE are the most frequently used.